The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/molecules27217337
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Chemotypes and Genetic Variability of Cinnamomum verum Leaf Samples Commercialized and Cultivated in the Amazon

Abstract: Cinnamomum verum (Lauraceae), also known as “true cinnamon” or “Ceylon cinnamon” has been widely used in traditional folk medicine and cuisine for a long time. The systematics of C. verum presents some difficulties due to genetic variation and morphological similarity between other Cinnamomum species. The present work aimed to find chemical and molecular markers of C. verum samples from the Amazon region of Brazil. The leaf EOs and the genetic material (DNA) were extracted from samples cultivated and commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The chemical compositions of Cinnamomum verum can be varied depending on the geographical distribution. It has been reported that C. verum leaf essential oils cultivated in different regions reveal the existence of four chemotypes (eugenol, eugenol and safrole, benzyl benzoate, and linalool) (Xavier et al 2022). Previous work revealed that yields and compositions of essential oils from cassia bark and twigs vary significantly based on their origins (Li et al 2013a;Cen et al 2021), which may be related to environmental conditions such as altitude, sunlight, and soil type, as well as to cultivation conditions (Figueiredo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical compositions of Cinnamomum verum can be varied depending on the geographical distribution. It has been reported that C. verum leaf essential oils cultivated in different regions reveal the existence of four chemotypes (eugenol, eugenol and safrole, benzyl benzoate, and linalool) (Xavier et al 2022). Previous work revealed that yields and compositions of essential oils from cassia bark and twigs vary significantly based on their origins (Li et al 2013a;Cen et al 2021), which may be related to environmental conditions such as altitude, sunlight, and soil type, as well as to cultivation conditions (Figueiredo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…35 The variation in secondary metabolite composition could be due to genetic modifications correlated with the adaptation of particular plant species to their environment. 37 The term phenoplasticity was introduced to describe the change in pattern of volatiles within a species under the influence of abiotic stressors. 10 The characterization of EO composition and their chemotypes is very important, making it possible to determine potentially toxic compounds and not only valuable bioactivities 38 and particularly in health claims regarding the EO components.…”
Section: Chemotypesmentioning
confidence: 99%
“…The variation in secondary metabolite composition could be due to genetic modifications correlated with the adaptation of particular plant species to their environment 37 . The term phenoplasticity was introduced to describe the change in pattern of volatiles within a species under the influence of abiotic stressors 10 .…”
Section: Introductionmentioning
confidence: 99%